Integrasi Ilmu Ekonomi Islam Dan Akhlak Dalam Perspektif Filsafat Ilmu - Jefani Anastasya; Bulan Al-Mughni; Adinda Fitria Lestari; Juwita Gea Nanda; Nada Rizkia Amanda; Indira Ramadhani (CV. ITTC INDONESIA, 2026)
The integration of Islamic economics and morality is an important aspect in developing an economic system that is not only oriented toward material profit but also emphasizes moral and spiritual values. From the perspective of the philosophy of science, Islamic economics has characteristics that differ from conventional economics because it is derived from the Qur'an and Hadith, which contain principles of justice, balance, responsibility, and public welfare. This study aims to analyze the integration of Islamic economics and morality from the perspective of the philosophy of science and to explain the importance of implementing both in modern life. The research method used is qualitative research with a library research approach through the collection of data from the Qur'an, Hadith, books, journals, and related literature. The results of the study indicate that the integration of Islamic economics and morality can create a more just, humane, and sustainable economic system. Moral values such as honesty, trustworthiness, justice, and social responsibility serve as the main foundation in economic activities, thereby preventing economic practices that contradict Islamic principles, such as usury (riba), uncertainty (gharar), fraud, and exploitation. Therefore, morality becomes the primary foundation in the development of Islamic economics aimed at achieving prosperity in both this world and the hereafter.